# Solve for y cube root of 15y=-3

15y3=-3
To remove the radical on the left side of the equation, cube both sides of the equation.
15y33=(-3)3
Simplify each side of the equation.
Multiply the exponents in ((15y)13)3.
Apply the power rule and multiply exponents, (am)n=amn.
(15y)13⋅3=(-3)3
Cancel the common factor of 3.
Cancel the common factor.
(15y)13⋅3=(-3)3
Rewrite the expression.
(15y)1=(-3)3
(15y)1=(-3)3
(15y)1=(-3)3
Simplify.
15y=(-3)3
Raise -3 to the power of 3.
15y=-27
15y=-27
Divide each term by 15 and simplify.
Divide each term in 15y=-27 by 15.
15y15=-2715
Cancel the common factor of 15.
Cancel the common factor.
15y15=-2715
Divide y by 1.
y=-2715
y=-2715
Simplify -2715.
Cancel the common factor of -27 and 15.
Factor 3 out of -27.
y=3(-9)15
Cancel the common factors.
Factor 3 out of 15.
y=3⋅-93⋅5
Cancel the common factor.
y=3⋅-93⋅5
Rewrite the expression.
y=-95
y=-95
y=-95
Move the negative in front of the fraction.
y=-95
y=-95
y=-95
The result can be shown in multiple forms.
Exact Form:
y=-95
Decimal Form:
y=-1.8
Mixed Number Form:
y=-145
Solve for y cube root of 15y=-3

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top